2015
DOI: 10.1021/am507522r
|View full text |Cite
|
Sign up to set email alerts
|

Self-Poled Transparent and Flexible UV Light-Emitting Cerium Complex–PVDF Composite: A High-Performance Nanogenerator

Abstract: Cerium(III)-N,N-dimethylformamide-bisulfate [Ce(DMF)(HSO4)3] complex is doped into poly(vinylidene fluoride) (PVDF) to induce a higher yield (99%) of the electroactive phases (β- and γ-phases) of PVDF. A remarkable enhancement of the output voltage (∼32 V) of a nanogenerator (NG) based on a nonelectrically poled cerium(III) complex containing PVDF composite film is achieved by simple repeated human finger imparting, whereas neat PVDF does not show this kind of behavior. This high electrical output resembles th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
130
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(135 citation statements)
references
References 48 publications
5
130
0
Order By: Relevance
“…10,50 Storing the generated energy and driving functional electronic devices require a regulated DC power supply (voltage) while piezoelectric harvesters generate time-varying voltages, therefore, the rectification is essential. 10,50 Storing the generated energy and driving functional electronic devices require a regulated DC power supply (voltage) while piezoelectric harvesters generate time-varying voltages, therefore, the rectification is essential.…”
Section: View Article Onlinementioning
confidence: 99%
See 2 more Smart Citations
“…10,50 Storing the generated energy and driving functional electronic devices require a regulated DC power supply (voltage) while piezoelectric harvesters generate time-varying voltages, therefore, the rectification is essential. 10,50 Storing the generated energy and driving functional electronic devices require a regulated DC power supply (voltage) while piezoelectric harvesters generate time-varying voltages, therefore, the rectification is essential.…”
Section: View Article Onlinementioning
confidence: 99%
“…For the past few decades, energy harvesting from environmental noise, friction, biomechanical, thermal, and low-frequency mechanical deformation has created a huge impact on the energy sector and thus the scientific community. [2][3][4][5][6][7][8][9][10][11][12] A variety of piezoelectric materials, such as BaTiO 3 , PbZr x Ti 1Àx O 3 (PZT), ZnO, ZnSnO 3 , GaN, and piezoelectric polymers have been examined in diverse forms. 5 The harvested energy is sufficient for the operation of small electronic devices in an aperiodic manner using energy storage devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Over the years, many different techniques have been used to substitute the electrical poling in the β-phase containing PVDF films such as nanoparticle doping, hydrated salt film, and Langmuir−Schaefer methods where the use of typical polingsteps was avoided. 1,2,15 In this work, we have doped the PVDF matrix with condensed nanostructured DNA to prepare self-poled β-phase containing PVDF films and to subsequently fabricate flexible NGs based on these films. DNA is a complex biopolymer with promising physical and electrical properties.…”
mentioning
confidence: 99%
“…For metal-oxide nanomaterials, because the high surface-to-volume ratio and surface defect of nanostructures, which made the metal-oxide nanomaterials are quite sensitive for the environment variation [19][20][21][22][23][24][25][26] . Many articles reported that Schottky contact mechanism can enhance the performance of metal-oxide nanomaterials, such as piezotronic devices 27,28 , nanogenerators [29][30][31][32] and nanosensors 20,[33][34][35][36][37][38][39] .…”
Section: Introductionmentioning
confidence: 99%